APLIKASI VIRTUAL TOUR FAKULTAS TEKNIK BERBASIS ANDROID MOBILE - Mide, Baharuddin; Masnur, Masnur (Jurnal Sintaks Logika, 2021)
UMPAR at the age of 18 has walked through two phases, namely; the pilot phase, and the development phase.. The high school, namely STKIP Muhammadiyah Parepare at that time, fostered three study programs, namely the Mathematics Education, English Education and Non-Formal Education (PLS) study programs. The effort to transform into a university was initiated by Drs. Said Amir Anjala, M as well as the First Rector. Unity supports all file formats, especially common formats such as all formats from artapplications. Unity is compatible with 64 bit versions, can operate on Mac Os x, Windows and Can produce games for mac, windows, Wii, iphone, ipad and Android. The research method used is Literature Study and Observational Research. In making this application using the C # programming language. The need for making a virtual tour application in taking pictures using the google camera application. This research produces games that can be played offline on all computers with low specifications and also on Android smartphones.